Eksplorasi Etnomatematika pada Monumen Perjuangan Rakyat Bali - Putu Wulan Cahayaningrat; Ni Wayan Dewi Anastasya Pratiwi; Ni Putu Monikha Alvionitha; I Gusti Ayu Made Srinadi (Journal on Education, 2024)
Indonesia's cultural wealth as an ancestral heritage requires protection so that the values of wisdom are preserved. In the era of globalization, education has an important role in shaping character and passing on cultural heritage. The ethnomathematics approach, which combines mathematics and culture, is a bridge to integrate culture in education. An ethnomathematics exploration of the Monument to the People's Struggle in Bali reveals mathematical concepts in the structure of the historic building. This research used an ethnographic and exploratory approach with a focus on the Bali People's Struggle Monument. Data consisted of observation, literature study, and documentation. Analysis was conducted to identify mathematical concepts, especially in geometry, using a taxonomy approach. The Monument to the Struggle of the Balinese People reflects the story of the play of Mandara Giri with the symbols of Lingga and Yoni. The building structure has an 8-square plan and the Asta Dala lotus flower. The symbol of struggle is reflected in the number of steps, the Supreme pillar, and the height of the monument, depicting the date of the Proclamation of Indonesian Independence. In the ethnomathematics exploration, geometry concepts such as square, octagon, right triangle, trapezoid, rectangle, circle, isosceles triangle, parallelogram, and tube were identified in the building structure of the Bali People's Struggle Monument.